ANALYSIS OF THE IMPLEMENTATION OF DIGITAL GAMES IN MULTIMEDIA EDUCATIONAL RESOURCES - Хорошевська, Ірина (SWorldJournal, 2025)
The paper analyses the implementation of digital games as important interactive components of learning in multimedia educational resources (courses, complexes, etc.). It is noted that the implementation of game elements contributes to increasing user moti